المواقع الاعرابية لاسم (الجلالة) في (سورة نوح) وأثره في المعنى - د. عبد الباقي محمد البرير يوسف (White Nile Journal for Studies and Research, 2019)
The name (majesty) of the beautiful names that feel safe and safe and tranquility of the slave. God Almighty is the Lord of all things and Creator, capable of it, does not come out anything about his Lordliness, and everyone in the heavens and the earth a slave in his grip. Majesty. God, the Lord in this research and its position in the narrative of Noa The literary sites of the name of the majesty and its impact on the meaning allowed the reader to trace the Qur'anic text in a way that makes it understand many aspects, including the diversity of the word and its significance, including the diversity of expression movements, all leading to a miraculous text that fails to complete its systems and human creation. There is an urgent need to trace the geographical locations of the name of the majesty and the difference in meaning as a study in Surah Noah, in order to show the effect of these sites on diversifying the meanings according to the Qur'anic verses in several places of Surah Noh. The destination was the meanings of the Quran and its commentary. In this study, I followed the different aspects of the expression of the name of the majesty and the impact of that in the concerned, and then reached the important results I mentioned at the conclusion of this study